Analisis Teknik Pengambilan Gambar Sinematografi Adegan Suspense dalam Film Animasi 3D “Ficusia" - Tama, Diella Marfika; Prasetiya, Happy Yugo (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2025)
In the world of 3D animated films, there is something in great demand among people today. Creating 3D animated films is not significantly different from making movies in general. Especially in shooting techniques, also commonly known as cinematography. The quality of the graphics and narration in the film will have a significant impact if you apply good cinematographic methods. As for the film "Ficusia", cinematographic shooting techniques play a crucial role in creating tense moments that build suspense and maintain the audience's interest throughout the story. The purpose of this study is to identify and describe the suspension formed by camera angle, shot type, and camera movement in the 3D animated film "Ficusia". This research employs descriptive-qualitative research methods, utilising theories to analyse the research through the lens of camera angle cinematography, types of shots, and camera movement. The results of this study successfully identified and described the suspension formed by camera angle, type of shot, and camera movement in the 3D animated film "Ficusia". The results of this study also show that the use of cinematographic techniques, such as camera angle, shot type, and camera movement, plays a significant role in creating suspense in scenes from the 3D animated film "Ficusia".